MiR-520a-3p Inhibited Macrophage Polarization and Promoted the Development of Atherosclerosis via Targeting UVRAG in Apolipoprotein E Knockout Mice - Qi, Jing Rui; Zhao, Dian Ru; Zhao, Li; Luo, Fan; Yang, Mei (Frontiers in Molecular Biosciences, 2021)
Atherosclerosis (AS), a kind of chronic inflammatory blood vessel disease, is a main cause of cardiovascular disease, which is a leading cause of mortality around the world. Accumulation of macrophages induced by inflammation contributes to AS development. It has been indicated that microRNAs (miRNAs) are involved in the process of AS. However, the pathway and gene miRNAs targeting are poorly understood. Here we reported that miR-520a-3p was increased in mice with AS and silencing of miR-520a-3p attenuated AS process. Furthermore, inhibition of miR-520a-3p increased the expression of α-SMA and collagen. In addition, miR-520a-3p silencing inhibited the expression of M1 macrophage polarization markers and pro-inflammatory genes and promoted the M2 macrophage polarization. What’s more, forced expression of miR-520a-3p diminished IL4/IL13 induced macrophage autophagy via targeting UVRAG. Collectively, our study reveals the role of miR-520a-3p in macrophage polarization and suggests the potential of miRNA as a novel treatment target of AS.